The evolution of plants and landscapes in traditional Malay houses of rural Perak - Mohd Hussain, Nur Huzeima; Zakaria, Ahmad Zamil; Amir, Atikah Raihanah (2025)
The transformation of traditional Malay house landscapes in rural Perak has become increasingly significant in light of rapid urbanization, socio-economic shifts, and environmental concerns. This study aims to analyze the evolution of plant selection and landscape changes within these dwellings. By examining both historical and contemporary practices, the research seeks to identify key plant species, their roles, and the factors influencing landscape transformations from years before 2010 to after 2020. Through field surveys, archival research, and interviews with local residents, the study investigates how traditional plant arrangements have adapted to socio-economic, cultural, and environmental shifts. Findings reveal that plants serve multiple functions, such as providing food sources, medicinal benefits, shade, and privacy, while also playing a role in cultural expression and environmental adaptation. Traditionally cultivated species include Tapioca spp., Cocos nucifera, banana trees (Musa spp.), and pegaga (Hydrocotile asiatica). However, due to urbanization, economic pressures, and ecological concerns, plant selection and garden layouts have undergone transformations over time. This study further examines the socio-cultural and ecological factors influencing these changes, including modernization, the pandemic, and lifestyle shifts. The research emphasizes the importance of preserving traditional landscape elements to maintain cultural identity and promote environmental sustainability. By bridging past and present landscaping practices, this study provides insights into integrating traditional horticulture with contemporary rural development. Ultimately, this research contributes to understanding the interplay between traditional architecture and horticulture, as well as the preservation of cultural heritage and the creation of sustainable rural landscapes.